Polio eradication in the African Region on course despite public health emergencies. Issue 9 (1st March 2017) - Okeibunor, Joseph C.; Ota, Martin C.; Akanmori, Bartholomew D.; Gumede, Nicksy; Shaba, Keith; Kouadio, Koffi I.; Poy, Alain; Mihigo, Richard; Salla, Mbaye; Moeti, Matshidiso R.
Abstract: The World Health Organization, African Region is heading toward eradication of the three types of wild polio virus, from the Region. Cases of wild poliovirus (WPV) types 2 and 3 (WPV2 and WPV3) were last reported in 1998 and 2012, respectively, and WPV1 reported in Nigeria since July 2014 has been the last in the entire Region. This scenario in Nigeria, the only endemic country, marks a remarkable progress. This significant progress is as a result of commitment of key partners in providing the much needed resources, better implementation of strategies, accountability, and innovative approaches. This is taking place in the face of public emergencies and challenges, which overburden health systems of countries and threaten sustainability of health programmes. Outbreak of Ebola and other diseases, insecurity, civil strife and political instability led to displacement of populations and severely affected health service delivery. The goal of eradication is now within reach more than ever before and countries of the region should not relent in their efforts on polio eradication. WHO and partners will redouble their efforts and introduce better approaches to sustain the current momentum and to complete the job. The carefully planned withdrawal of oral polio vaccine type II (OPV2) with an earlier introduction of one dose of inactivated poliovirus vaccine (IPV), in routine immunization, will boost immunity of populations and stop cVDPVs. Environmental surveillance for polio viruses will supplement surveillance for AFP and improve sensitivity of detection of polio viruses.